Variabilidade espacial de atributos químicos de um Latosso vermelho-amarelo e de produção de laranja Var. folha murcha no sul do estado do Espírito Santo - Zini Junior, Alaert (2008)
The orange is among the agricultural crops of greatest importance to the Brazilian economy, bringing guarantee of income and subsistence, especially for small and medium rural producers. In view of the current state of nutritional management of culture ad